2021
DOI: 10.53365/efood.k/147019
|View full text |Cite
|
Sign up to set email alerts
|

Xanthine oxidase targeted model setup and its application for antihyperuricemic compounds prediction by in silico methods

Abstract: To achieve potential alternatives for hyperuricemia therapeutics, a novel structure-docking energy relationship model was established for high-throughput screening inhibitors of xanthine oxidase (XO). Molecular docking was performed between XO and 311 natural compounds from 6 traditional Chinese herbs. Then, structure-docking energy relationship model was simulated between molecular docking energy and 63 molecular descriptors by multiple linear regressions (MLR), principal component regression (PCR), and artif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 21 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…Structural comparison was carried out by homology modeling, AlphaFold modeling, and 3A4A commonly used in the literature. , The results showed that the structures of several α-glucosidase based on 3A4A modeling, 3AXH modeling, 3AJ7 modeling, Alphafold modeling, and commonly used 3A4A were very similar (Figure A), and the 3D diagrams of the five structures were close to the coincidence state. Therefore, the overall quality factor, Ramachandran plot, and residues in the most favored regions were used to further evaluate the differences in the structure of the constructed α-glucosidase (Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…Structural comparison was carried out by homology modeling, AlphaFold modeling, and 3A4A commonly used in the literature. , The results showed that the structures of several α-glucosidase based on 3A4A modeling, 3AXH modeling, 3AJ7 modeling, Alphafold modeling, and commonly used 3A4A were very similar (Figure A), and the 3D diagrams of the five structures were close to the coincidence state. Therefore, the overall quality factor, Ramachandran plot, and residues in the most favored regions were used to further evaluate the differences in the structure of the constructed α-glucosidase (Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…19 In a previous study, we found that in the HK2 hyperuricemia cell model, pueraria ethanol extract significantly reduced the uric acid content in the supernatant compared with the model group. 20 In addition, in a liver organoid hyperuricemia model, pure puerarin was also found to have a uric acid-lowering effect. 21 Therefore, peptides and polyphenols may be considerable targets agent for rebalance uric acid levels in hyperuricemia patients.…”
Section: Food and Function Paper 4 Discussionmentioning
confidence: 97%
“…At present, the research methods at the forefront of stereochemistry basically focus on the combination of computational chemistry and tradition, such as computing ECD, computing optical rotation, amber software computing aided identification, and full spectrum calculation. The relative or absolute configuration can be effectively determined by comparing the calculated and experimental values (Beniddir et al, 2021; Hou et al, 2022; Tian et al, 2021). By 2D‐NMR and computational NMR methods we can determine the relative conformation ( α, β , etc., Figure 4) of e.g.…”
Section: Identification Of Stereo Structurementioning
confidence: 99%